Effective Acid Mine Drainage Treatment Using Natural Zeolite And Hydrated Lime (Pengkalan Hulu) - Nor, Nurfadzlin Syakina Md (Universiti Sains Malaysia, 2017)
Acid mine drainage is the new focus faced by industries of quarries and mining worldwide due to the health effects and environmental effect it can potentially bring to the surrounding communities. Of particular concern are the heavy metal ion that fall into the submicron range and soluble in the water, which have been shown to cause more grievous health effect than coarse particle. The river water is the main source of water for various uses and purposes where the contamination due agricultural activities and mining activities in this area does affect the stream which is obviously danger to the surrounding. For today, many research has been done for acid mine drainage however less is done on real acid mine drainage. This thesis present the results of a study conducted in Kelian Intan, Pengkalan Hulu,Perak where real acid mine drainage water sample is taken to be treated. This paper is purposed to investigate the effectiveness of which media (hydrated lime or natural zeolites) to treat acid mine drainage from this area rather than usually study that used simulated acid mine drainage water. Even though close monitoring on the acid mine drainage has been done, but this problem is still affecting the area. The project is important as to comply standard set by the Department of Environment and Mineral Department of Geoscience which is intended to protect environmental quality. Hence, if this project able to manipulate the parameter for water quality, we can improve its quality to find better solution to this problem.